What the 2018 (and 2020) elections mean for U.S. trade policy - Craig VanGrasstek (European Centre for International Political Economy (ECIPE), 2018)
The 2018 congressional elections put Democrats back in control of the House of Representatives, and thus returned divided government to Washington, but the meaning of these results for U.S. trade policy remain enigmatic. On the one hand, effective trade policymaking requires either unified government or a sense of comity between the branches. With neither of those conditions now prevailing, the prospects are high for gridlock over the next two years. On the other hand, trade is the one issue where Trump is more closely aligned with the Democrats than he is with the traditionalists in his own party. This suggests that there may be room for cooperation in the 116th Congress (2019-2020), but those prospects are further complicated by struggles within both parties. We may now be witnessing their realignment on trade, even if it takes at least one more electoral cycle to sort out the switches. Republicans must decide in 2020 whether to renominate the first truly protectionist president in nearly a century. Trade could be a key issue in a contested nomination fight, and even if Trump prevailed he might still be weakened by the challenge. If Trump were to win reelection, and to bring a new bunch of economic nationalists into Congress, his party's protectionist retreat may pass the point of no return. The 2020 race could also be an important turning point for the Democrats. It is possible that a bold candidate might pull a "reverse Trump" by defying the party's trade-skeptical orthodoxy and - if that candidate were to win - restore U.S. leadership in trading system. That potential may be more aspirational than realistic.
Keywords: 330